The Factors of Destination Image on Tourist Site in Kab. Garut - Yegi Esarianita (Prosiding Industrial Research Workshop and National Seminar, 2018)
This study being done to identify the destination image of destination place in Kab. Garut by using the cognitive and affective image. The methodology that being used in this study are both qualitative and qualitative approach to help on designing the questionnaire. The questionnaire was spreaded in some populare tourist site of Kab. Garut, with the total of respondents are 300, the respondents are those who ever visits or on their visit to destination place in Kab. Garut. The test the been done for this study are the descriptive test, validity test, and analysis factor. The aim of this study are 1) to identify the indicators that represent the destination image of Kab. Garut; 2) to find out the factors that build up the destination image of Kab. Garut. The results shown that there 7 factors that build up the destination image of Kab. Garut, there are natural attraction, affective, cost, weather, environment, accessability and traffic.